BIOACCESSIBILITY STUDIES OF POTENTIALLY TOXIC ELEMENTS IN DUST FROM OFFICES - Oluwaseun H., Anselm; Abosede A, Badeji; Oluwabusayomi A., Ibrahim; Hammed O., Ameen (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Potentially toxic elements are commonly referred to as heavy metals which are toxic and cannot be broken down. Potentially toxic elements are known to have a negative impact on human health especially children through oral ingestion, dermal and inhalation. In this study, the total metal concentration was determined in dust samples from selected offices of some tertiary institutions. Four dust samples were collected from different locations using a brush and plastic scoop. Afterwards, dust samples were naturally air dried and sieved through a 45μm mesh sieve and then acid digested. Results of the atomic absorption spectroscopy (AAS) analysis of the dust samples revealed the order of accumulation of cadmium and manganese in all sample locations. Contamination factor of Cd and Mn in all the four tertiary institutions were of low concentration. Also, the carcinogenic and non-carcinogenic risk was calculated based on the model developed by United States Environmental Protection Agency. For human health risk, the order of decreasing risk were ingestion >dermal>inhalation. This study shows that dusts from offices have effect on humans working in the office as it is the accumulation of settled toxic elements and humans spend more time indoors than outdoors.